2012
DOI: 10.1017/s0317167100013226
|View full text |Cite
|
Sign up to set email alerts
|

Eye Exercises for Treatment of Idiopathic Cranial Nerve VII Paresis: Pilot Study

Abstract: 1 . Loss of facial nerve function leads to facial disfigurement, increased salivation, alteration of taste as well as ocular complications. Decreased orbicularis oculi muscle strength can lead to ocular surface and eyelid problems such as epiphora, lagophthalmos, paralytic ectropion and exposure keratopathy. Loss of corneal protection can lead to corneal ulceration and potential blindness if treatment is delayed 2 . Treatment usually consists of a combination of eye lubrication, eyelid taping and, in severe ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…47 Characteristics of included studies: The 19 individual studies shown in Table 2 included, seven randomised controlled trials (total no. of subjects = 354); one quasi-experimental study (n = 16 patients) 48 ; two pilot studies (n = 37 patients) 49,50 ; and nine non-experimental observational studies (n = 447 patients). Observational studies varied in High their design: three were cohort studies (n = 169 patients) [51][52][53] ; two were retrospective studies (n = 101 patients) 54,55 ; three used group comparisons (n = 164 patients) [56][57][58] ; and one a small clinical study of 13 patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…47 Characteristics of included studies: The 19 individual studies shown in Table 2 included, seven randomised controlled trials (total no. of subjects = 354); one quasi-experimental study (n = 16 patients) 48 ; two pilot studies (n = 37 patients) 49,50 ; and nine non-experimental observational studies (n = 447 patients). Observational studies varied in High their design: three were cohort studies (n = 169 patients) [51][52][53] ; two were retrospective studies (n = 101 patients) 54,55 ; three used group comparisons (n = 164 patients) [56][57][58] ; and one a small clinical study of 13 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Two were randomised trials, 57 , 66 one was a quasi-experimental study, 48 and two were small pilot studies. 49 , 50 In terms of methodological flaws all, except one study, 60 were at risk of bias for failing to blind participants when outcomes were based on patient-reported measures. One high-quality study failed to achieve the required sample size, with a significant number of severe facial palsy patients in the control group dropping out in order to access physical therapy which was shown to be improving outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eye exercises are also practiced to enhance sports performance and used during yoga to promote general well-being [2]. However, few studies exist on evaluating the outcomes and efficacy of this type of therapy [1], [3][9]. One such study found a measurable effect of eye exercise in patients with convergence problems [10].…”
Section: Introductionmentioning
confidence: 99%